THE EFFECT OF ECONOMIC GROWTH ON ISLAMIC BANKING PROFITABILITY IN THE PHILIPPINES - Ibnohajad, Al-Ameen; Kawasan, Gary; Sali, Najeeb Razul (Journal of Management and Islamic Finance, 2025)
This paper investigated the economic history of Islamic banks in the Philippines, particularly the effect of the economy on its profitability. Net income of the Islamic bank was used as proxy for the bank’s profitability while GDP per capita and inflation rate in the country were used as proxy to represent the economy. Each variable was composed of 68 data points starting from first quarter of 2002 to the fourth quarter of 2019. Using Vector Error Correction Model (VECM) it finds that there is no long-run relationship running from the economy to Islamic banking profitability. The short-run test revealed that there was enough evidence to show that both GDP per capita and inflation, statistically significantly affected the financial growth of the net income of Islamic banking in the Philippines. This study concluded that Islamic banking profitability is not only determined by its internal operations, but external economic factors also affected the Islamic bank in the country.